Deforestation and agriculture in the tropics: carbon emissions and options for mitigation - Carter, S. (Wageningen University & Research, 2018)
Agriculture is the largest driver of deforestation globally, and this conversion of land from forests to agriculture, results in emissions which are contributing to climate change. This thesis focuses on exploring agriculture-driven deforestation at the country level, from the perspective of quantifying emissions, estimating the potential for mitigation, including identifying potential barriers to success, and highlighting enabling conditions for mitigation of these emissions. Efforts to reduce deforestation are being undertaken, for example through the mechanism REDD+; reducing emissions from deforestation and forest degradation and the role of conservation, sustainable management of forests and enhancement of forest carbon stocks in developing countries. At the same time, efforts are underway to try to reduce hunger by increasing food security (for example through the sustainable development goals (SDGs)). Competition for land can result when both these goals are pursued at the same time, because forested land is protected for carbon storage, while agricultural land is expanded (often into forests) to provide sufficient land for growing food. There are several ways in which both goals, forest protection and food security might be achieved together, and we focus on assessing the potential of two approaches which can potentially spare forested land. These approaches are: increasing production on existing agricultural land, and expanding agriculture onto non-forested available land. Emerging phenomena such as Large Scale Land Acquisitions (LSLA, otherwise known as land grabs) add to the complexity of the challenge, and we discuss the potential threat which LSLA has on forested land, and how to avoid LSLA for agriculture in forested land. A transformational change of the land sector is proposed to ensure that both goals can be met. Several ingredients are required to achieve a transformational change, and linking REDD+ to Climate Smart Agriculture (CSA) approaches is discussed. CSA interventions are those which are able to reduce emissions or store carbon while increasing the adaptive capacity of agriculture to climate change and increasing food production.